Evolved cellular network planning and optimization for UMTS and LTE - Song, Lingyang; Shen, Jia, 1977- (CRC Press, 2011)
Most books on network planning and optimization provide limited coverage of either GSM or WCDMA techniques. Few scrape the surface of HSPA, and even fewer deal with TD-SCDMA. Filling this void, Evolved Cellular Network Planning and Optimization for UMTS and LTE presents an accessible introduction to all stages of planning and optimizing UMTS, HSPA, and LTE cellular networks. Supplying a comprehensive explanation of the fundamental aspects of current and future cellular networks, the text starts with an overview of each type of network, including basic techniqu.